Innowacyjność, przedsiębiorczość, elastyczność - triada nowoczesnego zarządzania - Sus-Januchowska, Aleksandra (Innovation, Enterprise and Flexibility - Triad of the Present Organizations, 2006)
The purpose of this article is to define the main categories of modem organizations. Those categories are: innovativeness, enterprise and flexibility. Author decided to define these terms because in literature their usage is confusing and often have meaning that contradict each other.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 167-171